Interleukin-1α Mediates Ozone-Induced Myeloid Differentiation Factor-88-Dependent Epithelial Tissue Injury and Inflammation - Michaudel, Chloé; Maillet, Isabelle; Fauconnier, Louis; Quesniaux, Valérie; Chung, Kian Fan; Wiegman, Coen; Peter, Daniel; Ryffel, Bernhard (Frontiers in Immunology, 2018)
Air pollution associated with ozone exposure represents a major inducer of respiratory disease in man. In mice, a single ozone exposure causes lung injury with disruption of the respiratory barrier and inflammation. We investigated the role of interleukin-1 (IL-1)-associated cytokines upon a single ozone exposure (1ppm for 1h) using IL-1α-, IL-1β- and IL-18- deficient mice or an anti-IL-1α neutralizing antibody underlying the rapid epithelial cell death. Here we demonstrate the release of the alarmin IL-1α after ozone exposure and that the acute respiratory barrier injury and inflammation and airway hyperreactivity are IL-1α dependent. IL-1α signaling via IL-1R1 depends on the adaptor protein MyD88. Importantly, epithelial cell signaling is critical, since deletion of MyD88 in lung type I alveolar epithelial cells reduced ozone-induced inflammation. In addition, intratracheal injection of rmIL-1α in MyD88ACID mice led to reduction of inflammation in comparison with WT mice treated with recombinant. Therefore, a major part of inflammation is mediated by IL-1α signaling in epithelial cells. In conclusion, the alarmin IL-1α released upon ozone-induced tissue damage and inflammation is mediated by MyD88 signaling in epithelial cells. Therefore, IL-1α may represent a therapeutic target to attenuate ozone-induced lung inflammation and hyperreactivity.